Creative marketplaces as entrepreneurial micro ecosystems: Exploring incubation, collaboration, and social value creation - Setiawati , Liya; Istiqomah, Yuliani (Journal Economic Business Innovation, 2025)
Purpose: This research explores the impact of entrepreneurial micro ecosystem elements on entrepreneurial development including placemaking, social value creation and the role played by collaborative culture.Method: A quantitative explanatory design was employed with survey data from 312 creative entrepreneurs in Indonesia and analyzed utilizing SPSS as well as process macro (Model 7).Findings: The findings show that supportive ecosystem conditions boost entrepreneurial growth directly and indirectly with placemaking and social value creation functions. Culture of collaboration augments these relationships through trust, mutual learning and joint innovation. The analysis shows that social factors in creative marketplaces can turn structural advantages into an entrepreneurial achievement tradition, and that collaboration, particularly as it pertains to the creation of social value, underpins ecosystem efficiency and community renaissance.Novelty: This study integrates entrepreneurial ecosystem, social capital, and placemaking theories in a comprehensive framework, and places collaborative culture as a mediating mediator on the road to ecosystem-led entrepreneurship.Implications: The results offer policy and practical implications for policymakers, ecosystem designers, and entrepreneurs to generate collaboration-based ecosystems which have a balance between innovation, inclusion, and social cohesion as basis of sustainable economic development.